Enhancing Reliability of Series-Parallel Systems: A Novel Mathematical Model for Redundancy Allocation (European Journal of Pure and Applied Mathematics, 2025)
In reliability theory, series-parallel configuration systems provide a fundamental framework for examining the relationship between individual component lives and the overall system durability. This research examines the influence of several constraints, namely weight, volume, dimensions, and spatial limitations, on enhancing system reliability, specifically regarding spare components for standard oil burners, including nozzle tubes and electrode brackets. An Integrated Redundant Reliability Series-Parallel configuration system is systematically designed and evaluated utilizing the Lagrangean multiplier method, yielding real-valued solutions for essential parameters such as component quantities, component reliability, stage reliability, and overall system reliability. The study used the dynamic programming method to seek integer solutions, hence improving the accuracy and relevance of the reliability analysis.
Keywords: IRR Model, Series-Parallel Configuration, System Reliability, LAM Approach, DMM Approach